Blockchain Technology: Architecture, Applications, and Challenges - Kacheru, Goutham (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
This, together with the related term Bitcoin, was a revolution in blockchain as envisioned by the mystery character Satoshi Nakamoto up to 2008. All this changes the very way the foundations of digital exchange and storage were thought about: decentralized, transparent, immutable, the very fundamentals of Distributed Ledger Technology enabling safe data exchange without an intermediary. The blockchain is fundamentally a chain of blocks carrying information about transactions, including times and cryptographic hashes, each of these connecting to the previous one in one unbroken chain, for which no modification is viable. The whole design of Blockchain has been to solve a number of issues, including double spending, fraud, and inefficient records, with distributed nodes and consensus mechanisms such as Proof of Work and Proof of Stake, facilitated by cryptographic keys. Other areas beyond cryptocurrency where quite a number of innovative uses are cut across include supply chain, healthcare, financial, and real estate sectors. For example, while the supply chain process is being promoted to become effective and transparent in order to ensure the origin and quality of the product, adding to the guarantee that the user's personal health information will not be accessed and tampered with, blockchain uses smart contracts in automating agreement processes within the contract. All of them are expecting cost reduction, operating efficiencies enhancement, enhanced securities of many industries. Anyhow, there exist quite a number of serious obstacles standing in the way of the wide application of blockchain technology. Firstly, the problem of scalability has still been an issue whereby the network performance tends to be problematic when users are increased. Besides, energy wasting cannot be ignored-apparently mostly a challenge from the PoW kind of system proved to be consuming too much energy, standing big on the road to sustainability. Of course, the mere lack of any kind of international rules and standards is already a complication in making them work. It also underlines failures in the adoption of the system or in decentralizing and is still an open technical and organizational challenge on how to combine blockchain with traditional structures. Their solutions require compounding ideas: sharding of blockchain to make it big, off-chain solutions for the blockchain to be many but thin, and provision of amicable solution consensus mechanisms for environmental conservation. Besides coherent policy vision, in addition to the existing cornerstones of regulation besides well-laid-out standards of interoperability, it is important to create confidence and give a road map across different industries. This paper hereby conceptually reviews the literature with respect to how the blockchain technology was designed to show revolutionary capability in the different fields and what keeps on tormenting it with its future.KEYS: Blockchain technology; Distributed Ledger; Decentralization; Cryptographic keys; Consensus mechanisms; Proof of Work; Proof of Stake; Smart contracts; Supply chain management; Data immutability; Transparency; Scalability; Energy consumption; Challenges to regulatory bodies; Security vulnerability; Sharding; off- chain processing; Interoperability; Applications using blockchain; Architecture of blockchain.